Front Cover: Preparation of Naphthalene Dianhydride Bithiophene Copolymers by Direct Arylation Polycondensation and the Latent Pigment Approach (ChemPlusChem 9/2019). Issue 9 (17th July 2019) - Sanzone, Alessandro; Cimò, Simone; Mattiello, Sara; Ruffo, Riccardo; Facchinetti, Irene; Bonacchini, Giorgio E.; Caironi, Mario; Sassi, Mauro; Sommer, Michael; Beverina, Luca
Abstract : The front cover shows the thermally induced transformation of a soluble and electron‐rich naphthalenetetraester–bithiophene copolymer into the corresponding insoluble and electron‐poor naphthalenetetraanhydride derivative. The combination of monochromatic squares, inspired by the work of Josef Albers, shows the color change involved in the transformation. The stylized circuitry in the background hints at applications in printed electronics. Details are given in the Full Paper by L. Beverina, M. Sommer, and co‐workers on page 1346 in Issue 9, 2019 (DOI: 10.1002/cplu.201900210 ).